Colon and rectal surgery abdominal operations - Wexner, Steven D.; Fleshman, James; Fischer, Josef E. 1937- (Master techniques in general surgery, 2019)
Master Techniques in General Surgery : Colon and Rectal Surgery : Abdominal Operations is a volume in a series that presents common and advanced procedures in the major subspecialities of general surgery. The series is overseen by Josef F. Fischer, MD, editor of the classic two-volume reference Mastery of Surgery. Master Techniques in General Surgery : Colon and Rectal Surgery : Abdominal Operations is written by acknowledged master surgeons, emphasizes surgical procedures, and is illustrated with original full-color drawings. The contributors fully explain their preferred techniques in step-by-step, thoroughly illustrated detail, assess indications and contraindications, offer guidelines on preoperative planning, and discuss outcomes, complications, and follow-up.Coverage includes left and right colon resections performed open and laparoscopically, colectomies, proctocolectomies, restorative and reconstructive techniques for proctocolectomy and pelvis reconstruction, stoma construction and how to repair complications of stoma construction, and treatment of rectal prolapse. A companion website will offer fully searchable content of the book, an image bank, and procedural videos"--Provided by publisher